Synthesis and Spectral Studies of 8-Alkyl/Phenyl-16H- Dinaphtho [2,1-d : 1´ ,2´ -g][1, 3, 2] Dioxaphosphocin 8-oxides and 2,10-Dichloro-6-Alkyl/Phenyl-12H-Dibenzo [d, g][1, 3, 2] Dioxaphosphocin 6-Oxides < - Devendranath Reddy, C.; Suryanarayana Reddy, R.; Naga Raju, C. (Asian Journal of Chemistry, 2010)
Two series of novel 8-alkyl/phenyl-16H-dinaphtho [2,1-d : 1´, 2´-g] [1, 3, 2] dioxaphosphocin 8-oxides and 2,10-dichloro-6-alkyl/phenyl- 12H-dibenzo [d, g][1, 3, 2] dioxaphosphocin 6-oxides were synthesised and their structures established by IR, 1H NMR and mass spectral data. A few of these compounds were also evaluated for their toxicity in insects.